Response of spinach and komatsuna to biogas effluent made from source-separated kitchen garbage - Furukawa, Yuichiro; Hasegawa, Hiroshi (Wiley, 2006)
Recycling of kitchen garbage is an urgent task for reducing public spending and environmental burdens by incineration and/or landfill. There is an interesting regional effort in Ogawa, Saitama prefecture, Japan, in which source‐separated kitchen garbage is anaerobically fermented with a biogas plant and the resultant effluent is used as a quick‐release organic fertilizer by surrounding farmers. However, scientific assessments of fertilizer values and risks in the use of the effluent were lacking. Thus, a field experiment was conducted from 2003 to 2004 in Tohoku National Agricultural Research Center to grow spinach (Spinacia oleracea L.) and komatsuna (Brassica rapa var. perviridis L. H. Bailey) for evaluating the fertilizer value of the kitchen garbage effluent (KGE), nitrate, coliform group (CG), Escherichia coli, fecal streptococci (FS), and Vibrio parahaemolyticus concentrations of KGE and in the soil and the plant leaves. A cattle manure effluent (CME) and chemical fertilizers (NPK) were used as controls. Total nitrogen (N) and ammonium N concentrations of the KGE were 1.47 and 1.46 g kg−1, respectively. The bacteria tested were detected in both biogas effluents in the order of 2 to 3 log CFU g−1, but there was little evidence that the biogas effluents increased these bacteria in the soil and the plant leaves. At the rate of 22 g N m−2, yield, total N uptake, apparent N recovery rate, and leaf nitrate ion concentration at harvest of spinach and komatsuna in the KGE plot were mostly comparable to those in the NPK and CME plots. We conclude that the KGE is a quick‐release N fertilizer comparable to chemical fertilizers and does not cause contamination of CG, E. coli, FS, or V. parahaemolyticus in the soil and spinach and komatsuna leaves.